Pertambangan emas tanpa izin (PETI) dan kesejahteraan keluarga di sekitar wilayah pertambangan - Junaidi Junaidi (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
This study aims to 1) analyze the impact of illegal gold mining (IGM) on social, economic, and environmental conditions as well as the problems faced by families in the IGM area; 2) Formulate strategies for handling the impact of IGM on family welfare. The research was conducted in Pangkalan Jambu District, Merangin Regency, Jambi Province. The type of data used is primary data sourced from family respondents and informants in the area around mining. Data were collected through questionnaires, in-depth interviews, and Focus Group Discussions (FGD). The results of the analysis found that IGM activities in general have been able to grow new job opportunities and increase people's income. However, from social and environmental aspects, there are various negative impacts of IGM on family welfare. Therefore, in dealing with the impact of IGM on family welfare, three policy strategies are recommended, namely: 1) increasing family capacity; 2) strengthening the values ​​of local wisdom and social capital in society; 3) People's Mining Area and Small-Scale Mining programs. Keywords: Family welfare, Illegal gold mining, Income shock